Is the female sex associated with an increased risk for long-term cognitive decline after the first-ever lacunar stroke? Prospective study on small vessel disease cohort - Pavlovic, Aleksandra; Pekmezovic, Tatjana; Mijajlovic, Milija; Tomic, Gordana; Zidverc Trajkovic, Jasna (Frontiers in Neurology, 2023)
Background Sex is a significant determinant of survival and functional outcome after stroke. Long-term cognitive outcome after acute lacunar stroke in the context of sex differences has been rarely reported. Methods A cohort of small vessel disease (SVD) patients presenting with first-ever acute lacunar stroke and normal cognitive status has been evaluated 4 years after the qualifying event for the presence of cognitive impairment (CI) with a comprehensive neuropsychological battery. Differences in baseline clinical and neuroimaging characteristics were compared between sexes in relation to cognitive status. Results A total of 124 female and 150 male patients were analyzed. No difference was detected between the groups regarding age (p = 0.932) or frequency of common vascular risk factors (p > 0.1 for all). At the baseline assessment, women had more disabilities compared to men with a mean modified Rankin scale (mRS) score of 2.5 (1.5 in men, p < 0.0001). Scores of white matter hyperintensities (WMH) of presumed vascular origin and a total number of lacunes of presumed vascular origin on brain MRI were higher in women compared to men (p < 0.0001 for all). As many as 64.6% of patients had CI of any severity on follow-up, women more frequently (77.4%) than men (54.0%; p < 0.0001). Univariate logistic regression analysis showed that female sex, higher NIHSS and mRS scores, presence of depression, and increasing WMH severity were associated with an increased risk for CI. Multivariate regression analysis indicated that only depression (OR 1.74, 95%CI 1.25–2.44; p = 0.001) and WMH severity (OR 1.10, 95%CI 1.03–1.17; p = 0.004) were independently associated with the CI. Conclusion At the long-term follow-up, women lacunar stroke survivors, compared to men, more frequently had CI in the presence of more severe vascular brain lesions, but this association was dependent on the occurrence of depression and severity of WMH, and could not be explained by differences in common vascular risk factors.